THE RELATIONSHIP BETWEEN FINANCIAL LIBERALISATION AND HUMAN CAPITAL DEVELOPMENT IN NIGERIA - Nkechinyere R., UWAJUMOGU (Journal of Human Capital Development (JHCD), 2018)
Finance is a very important and critical ingredient in the growth and developmental process. This has led experts to propose that the financial sector should be closely monitored and organized. The objective of the study was to find out the relationship between financial liberalization and human capital development in Nigeria using quarterly data from 1993 to 2013. The study employed the ARDL method and found that financial liberalization has long run relationship with human capital development; though different measures of financial liberalization gave varying signs of the relationship between them and human capital development. On the basis of these findings, many recommendations were proffered which include economic stability (internal equilibrium) before financial liberalization; sustainable regulatory and supervisory framework; direction of credit to productive sectors etc. Keywords: financial liberalisation, human capital development, per capita income